The application of triple aim framework in the context of primary healthcare: A systematic literature review. Issue 8 (August 2018) - Obucina, M.; Harris, N.; Fitzgerald, J.A.; Chai, A.; Radford, K.; Ross, A.; Carr, L.; Vecchio, N.
Highlights: Operationalization of the Triple Aim framework varies across studies. Quality measures were based on locally available data and limited in scope. Inconsistency in the implementation of Triple Aim across all dimensions. Triple Aim can potentially measure changes in primary healthcare over time. Abstract: The Triple Aim framework is an increasingly popular tool for designing and assessing quality improvements in the health care sector. We systematically reviewed the empirical evidence on the application of the Triple Aim framework within primary healthcare settings since its inception almost a decade ago. Results show that primary healthcare providers varied in their interpretation of the Triple Aim framework and generally struggled with a lack of guidance and an absence of composite sets of measures for performance assessment. Greater clarity around application of the Triple Aim framework in primary healthcare is needed, especially around the selection and implementation of purposeful measures from locally available data. This review highlights areas for improvement and makes recommendations intended to guide future applications of the Triple Aim in the context of primary healthcare.